Web-Based Building Services Application (Case Study: CV Tirto Ardhi) - Fuad Asyhary, Mochamad; Eko Wulandari, Sri Hariani; Rahmawati, Endra (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2019)
CV Tirto Ardhi is a private company engaged in building services that has several services in the field of building services, namely building renovation, building services, interior / exterior design consultants, as well as rental of artisan and porters. The obstacle experienced by CV Tirto Ardhi is a service process that is less effective because it is manual. In service payment transactions are still manual so that when serving the buyer slowly and the report recap is still not neat in conveying data and information to the leadership, ordering is still difficult for customers outside the city. The solution designed is to make a building service application. This application can make building service payment transactions, can convey information through notification of web-based building service applications, and make building service transaction reports in a certain period in a system. The method used in the design is Waterfall (System Development Life Cycle). The stages used are planning, needs analysis, system design and programming, system implementation, and application testing. With the construction of the application services, CV Tirto Ardhi is able to manage payment services for building services and Company Profiles effectively. As well as companies can serve customers easily using the application, to process customer service building orders.